The Haifa Mediterranean Biennale 2010 : Household Goods. - Fainaru, Belu-Simion (Haifa : The Haifa Mediterranean Biennale, 2010)
Port workers ; Perjovschi, Dan ; Man, Victor ; Zarawi, Runi ; Wertman, Israel ; Gitai, Amos ; Ullman, Micha ; Shamia-Opher, Nati ; Schwartz, Buky ; Croitoru, Alexandra ; Knafo Klimor Architects ; Kliest, Albert ; Kallash, Muhammad Said ; Cavusoglu, Ergin ; Mahamid, Mannal ; Moldovan, Sebastian ; Diepens, Carina ; Brech, Christoph ; Akerman, Chantal ; Efrat, Benny ; Asai, Mariko ; Anders, Anna ; Milhem, Bohtaina Abu ; Sher, Angelika ; Karavan, Dani ; Fainaru, Belu-Simion ; Fatmi, Mounir ; Papadimitriou, Maria ; Manna, Jumana ; Muresan, Ciprian ; Tenger, Hale ; Van Ingelgem, Herman ; Heiman, Meirav ; Garabedian, Mekhitar ; Bejenaru, Matei ; Boltanski, Christian ; Bawayah, Raed ; Ekici, Nezaket ; Abergel, Eti ; Ebata, Kyoko
boek